Obacunone Protects Against Ulcerative Colitis in Mice by Modulating Gut Microbiota, Attenuating TLR4/NF-κB Signaling Cascades, and Improving Disrupted Epithelial Barriers - Luo, Xiaoping; Yue, Bei; Yu, Zhilun; Ren, Yijing; Zhang, Jing; Ren, Junyu; Wang, Zhengtao; Dou, Wei (Frontiers in Microbiology, 2020)
Obacunone, a natural limonoid compound abundantly distributed in citrus fruits, possesses various biological properties, such as antitumor, antioxidant, and antiviral activities. Recent studies suggested an anti-inflammatory activity of obacunone in vitro, but its efficacy on intestinal inflammation remains unknown. This study was designed to evaluate the effects and mechanisms of obacunone in ameliorating intestinal inflammation in a mouse model of inflammatory bowel disease (IBD). We found that obacunone efficiently alleviated the severity of dextran sulfate sodium (DSS)-induced mouse IBD by modulating the abnormal composition of the gut microbiota and attenuating the excessive activation of toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) signaling. The intestinal epithelial barrier was disrupted in DSS colitis mice, which was associated with activation of inflammatory signaling cascades. However, obacunone promoted the expression of tight junction proteins (TJP1 and occludin) and repressed the activation of inflammatory signaling cascades. In summary, our findings demonstrated that obacunone attenuated the symptoms of experimental IBD in mice through modulation of the gut microbiota, attenuation of TLR4/NF-κB signaling cascades, and restoration of intestinal epithelial barrier integrity.